2011
DOI: 10.7861/clinmedicine.11-6-524
|View full text |Cite
|
Sign up to set email alerts
|

The impact of twice-daily consultant ward rounds on the length of stay in two general medical wards

Abstract: -Excess average length of stay (ALoS) not only results in an increased cost to hospitals but also increases the risk of hospital-acquired infection and thromboembolism. Various factors suggested to affect ALoS have yet to demonstrate a significant impact in clinical practice. Increased consultant input has been identified as an important factor influencing ALoS. As a result, a radical and innovative consultant job plan, replacing twice-weekly with twice-daily ward rounds (WRs) on a university teaching hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Ward rounds are an established process for clinical review and connecting clinicians with patients. Historically, the ward round was framed as a process through which medical staff, generally accompanied by nurses, attended the bedside of patients and made clinical decisions (Ahmad, Purewal, Sharma, & Weston, ; Nikendei, Kraus, Schrauth, Briem, & Junger, ). In many settings, this traditional form of rounding continues today.…”
Section: Introductionmentioning
confidence: 99%
“…Ward rounds are an established process for clinical review and connecting clinicians with patients. Historically, the ward round was framed as a process through which medical staff, generally accompanied by nurses, attended the bedside of patients and made clinical decisions (Ahmad, Purewal, Sharma, & Weston, ; Nikendei, Kraus, Schrauth, Briem, & Junger, ). In many settings, this traditional form of rounding continues today.…”
Section: Introductionmentioning
confidence: 99%
“…5 One hospital has recently reported a reduction in average inpatient stay to 5.3 days, coincident with the introduction of twice-daily consultant ward rounds. 6 Nevertheless, demand frequently outstrips supply. Hospitals are often 'full' , with deleterious effects that include delayed patient flow, failure of specialty ward-based hospital systems and delayed or cancelled elective admissions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of senior clinicians is essential for decisions to be made regarding discharges. A study found that average LoS was significantly improved by daily consultant supervision [40].…”
Section: Managing Length Of Staymentioning
confidence: 99%